Studi Analisis Tentang Konsep Pelanggaran Orang Tua Yang Ditanggung Oleh Anak-Anaknya Berdasarkan Keluaran 20:5 - Dimas Andono Warih, Wahyu (SAGACITY : Journal of Theology and Christian Education, 2024)
This article discusses Exodus 20:5, the Bible verse that states that God "will repay the iniquities of parents on children and grandchildren to the third and fourth generations." The main focus is to analyze these meaning texts and understand how the concept of parental transgression can be borne by offspring. Through an exegetical approach, this article explores the literal and symbolic meaning of the verse. While some interpretations tend toward a literal understanding of the remission of sin, this analysis also considers symbolic meanings involving moral responsibility and psychological impact. In addition, this article highlights the theological and ethical framework of understanding related to the concept of resolving generational sin. Discussion involves consideration of the cultural context in which the text was written and how its moral message is relevant in the context of modern society. Thus, this article not only approaches the biblical text theologically, but also seeks its practical application in moral contexts and everyday life. The conclusion leads to a balanced understanding of personal responsibility and the collective impact of parental actions, taking into account the spiritual and ethical values that may be contained in the verse.